Impairment of GABAB receptor dimer by endogenous 14-3-3ζ in chronic pain conditions - Laffray, Sophie (Nature Publishing Group, 2012)
In the central nervous system, the inhibitory GABAB receptor is the archetype of heterodimeric G protein-coupled receptors (GPCRs). However, the regulation of GABAB dimerization, and more generally of GPCR oligomerization, remains largely unknown. We propose a novel mechanism for inhibition of GPCR activity through de-dimerization in pathological conditions. We show here that 14-3-3ζ, a GABAB1-binding protein, dissociates the GABAB heterodimer, resulting in the impairment of GABAB signalling in spinal neurons. In the dorsal spinal cord of neuropathic rats, 14-3-3ζ is overexpressed and weakens GABAB inhibition. Using anti-14-3-3ζ siRNA or competing peptides disrupts 14-3-3ζ/GABAB1 interaction and restores functional GABAB heterodimers in the dorsal horn. Importantly, both strategies greatly enhance the anti-nociceptive effect of intrathecal Baclofen in neuropathic rats. Taken together, our data provide the first example of endogenous regulation of a GPCR oligomeric state and demonstrate its functional impact on the pathophysiological process of neuropathic pain sensitization.